From problem to solution : Commonwealth strategies for reform (Commonwealth Secretariat LondonGB, 1995)
Develops a framework for the management of public service reforms, based on successful innovations and practical strategies which have been developed and implemented across the Commonwealth.
Additional copy located in the Office of the Secretary-General. Bibliography : p. 69